Relationship between patient-reported and objective measurements of hand function in patients with rheumatoid arthritis - S.M. Günay; Z. Tuna; D. Oskay (PAGEPress Publications, 2016)
Rheumatoid arthritis (RA) often results in impairments in upper extremities, especially in the small joints of hand. Involvement of hand brings limitations in activities of daily living. However, it is commonly observed that patient-reported functional status of hand does not always corresponds to their actual physical performance in the clinical setting. The aim of this pilot study is to investigate the relationship between patient self-reported and objectively measured hand functions in patients with RA. Twenty-six patients (51±13 years) with RA diagnosis participated in the study. Hand grip and pinch (lateral, bipod, tripod) strengths were measured and Jebsen Hand Function Test (JHFT) was performed for objective functional performance. Duruöz Hand Index and Beck Depression Inventory - Turkish version were completed by patients. Grip and all three-pinch strength results significantly correlated with Duruöz Hand Index scores (p<0.05). JHFT results except the sentence writing also correlated with the Duruöz scores (p<0.05). Our results showed that self-reported outcome scales might be used for determining functional level of hand in patients with RA in rheumatology practice. Objective quantitative functional tests are the best methods in evaluating functional level of hand, but require valid and reliable equipment with accurate calibration. Therefore, in case of unavailability of objective assessment tools, patient-reported scales may also reflect the real status of hand functions.